Conformity between Pacifier Design and Palate Shape in Preterm and Term Infants Considering Age-Specific Palate Size, Facial Profile and Lip Thickness - Gwendolin Sistenich; Claudius Middelberg; Thomas Stamm; Dieter Dirksen; Ariane Hohoff (MDPI AG, 2022)
This retrospective case-control study is the first to examine the spatial conformity between pacifiers and palates in 39 preterm infants (12 females, 27 males) and 34 term infants (19 females, 15 males), taking into account the facial-soft-tissue profile and thickness. The shape of 74 available pacifiers was spatially matched to the palate, and conformity was examined using width, height, and length measurements. In summary, the size concept of pacifiers is highly variable and does not follow a growth pattern, like infant palates do. Pacifiers are too undersized in width, length, and height to physiologically fit the palate structures from 0 to 14 months of age. There are two exceptions, but only for premature palates: the palatal depth index at 9-11 months of age, which has no clinical meaning, and the nipple length at <37 weeks of age, which bears a resemblance to the maternal nipple during non-nutritive sucking. It can be concluded that the age-size concept of the studied pacifiers does not correspond to any natural growth pattern. Physiologically aligned, pacifiers do not achieve the age-specific dimensions of the palate. The effects attributed to the products on oral health in term infants cannot be supposed.